Preparation method and application of rare earth doped ruthenium-based catalyst
By doping rare earth ruthenium-based multi-metal oxide electrocatalyst, the problems of slow redox reaction rate and insufficient catalyst stability in zinc-empty batteries are solved, and the high energy density, high power and long life of zinc-empty batteries are achieved.
Patent Information
- Application Number
- CN202411575294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
During the charging and discharging process of zinc-empty batteries, the redox reaction rate on the positive electrode of the air is slow, which limits the energy density and power of the zinc-empty batteries, and the stability of the catalyst is insufficient, affecting the cycle life.
A rare earth doped ruthenium-based multi-metal oxide electrocatalyst was used to prepare a catalyst with OER/ORR dual-function catalytic activity and stability through the high intrinsic OER activity and stability of RuO2 and combined with other metal elements and rare earth metals.
It significantly improves the energy density, high power and long life of zinc-air batteries, and meets the needs of zinc-air batteries with high energy density, high power and long life.
Smart Images

Figure HDA0005121636320000011 
Figure HDA0005121636320000012 
Figure HDA0005121636320000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis, and in particular to a preparation method and application of a rare earth-doped ruthenium-based catalyst. Background Art
[0002] China's installed capacity of renewable energy power generation, represented by solar and wind power, has achieved significant growth. By the end of June 2024, the installed capacity of solar and wind power generation reached 1.18 billion kilowatts, surpassing coal-fired power for the first time. Given the volatility of renewable energy power generation, the demand for efficient and reliable energy storage equipment and technologies, such as electrochemical energy storage and mechanical energy storage, has increased dramatically. Among various electrochemical energy storage devices, rechargeable zinc-air batteries have won widespread attention and research enthusiasm due to their safety, low cost and high energy density (1086W·h / kg). Although zinc-air batteries have made significant progress in materials and devices, the bifunctional catalytic activity and stability of air cathode catalysts remain the bottleneck for their large-scale application.
[0003] Zinc-air batteries rely on two key reactions: the oxygen evolution reaction (OER) during charging and the oxygen reduction reaction (ORR) during discharging. However, during the charging and discharging process, the OER and ORR reaction rates on the air cathode are slow, which severely limits the energy density and power of zinc-air batteries. At the same time, the cycle life of zinc-air batteries is also highly dependent on the stability of the catalyst. Although many catalysts with OER / ORR bifunctional catalysis have been developed, the zinc-air batteries composed of these catalysts still fail to meet the requirements of actual large-scale energy storage operation. Developing a catalyst with high OER / ORR bifunctional catalytic activity and stability is the key to the large-scale energy storage application of zinc-air batteries. By utilizing the high OER activity and stability of RuO2, and doping it with rare earth metals, combined with other metal elements, a multi-metal oxide catalyst can be prepared to achieve high OER / ORR bifunctional catalytic activity and stability, thereby meeting the needs of high energy density, high power and long life zinc-air batteries. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to propose a method for preparing a rare earth-doped ruthenium-based catalyst. The preparation method disclosed in the present invention has the advantages of simple operation process, low cost, environmental friendliness and easy large-scale preparation. The prepared catalyst exhibits excellent electrocatalytic performance, especially in terms of OER / ORR bifunctional catalytic activity and stability. The assembled zinc-air battery has excellent comprehensive performance and cycle stability.
[0005] In one aspect of the present invention, the present invention proposes a rare earth-doped ruthenium-based multinary metal oxide electrocatalyst. According to an embodiment of the present invention, the rare earth-doped ruthenium-based multinary metal oxide electrocatalyst is RE-MRuO2, RE is selected from rare earth elements, M is other metal elements, the content of RuO2 is not less than 50wt%, the content of rare earth elements is between 0-50wt%, and the content of metal elements is between 0-50wt%. Relying on the high intrinsic OER activity and stability of RuO2, combined with other metal elements, the catalyst has OER / ORR dual-functional catalytic activity and stability. On this basis, rare earth metal elements are doped to further enhance the catalytic activity and stability. Secondly, as an air cathode catalyst, the assembled zinc-air battery has the characteristics of high energy density, high power and long life, and shows great potential in large-scale energy storage.
[0006] According to an embodiment of the present invention, the rare earth-doped ruthenium-based multinary metal oxide electrocatalyst may further include at least one of the following additional technical features:
[0007] According to an embodiment of the present invention, the rare earth element includes one or more selected from scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu), and the other metal M is Pt (platinum), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn) and bismuth (Bi).
[0008] In another aspect of the present invention, the present invention also provides a method for preparing a rare earth-doped ruthenium-based multinary metal oxide electrocatalyst. According to an embodiment of the present invention, the method comprises:
[0009] 1) mixing and pretreating a mixture of a precursor salt, a template agent and a bulking agent to obtain a mixture,
[0010] 2) calcining and annealing the mixture to obtain a rare earth-doped ruthenium-based multinary metal oxide electrocatalyst,
[0011] The rare earth doped ruthenium based multinary metal oxide electrocatalyst is RE-MRuO2, RE is selected from rare earth elements, M is other metal elements, the content of RuO2 is not less than 50wt%, the content of rare earth elements is between 0-50wt%, and the content of other metal elements is between 0-50wt%. The inventors found that the content of RuO2 cannot be too low, otherwise the stability of the entire catalyst will be reduced, and the OER performance will also be reduced.
[0012] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0013] According to an embodiment of the present invention, the rare earth element includes one or more selected from scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu), and the other metal M is Pt (platinum), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn) and bismuth (Bi).
[0014] According to an embodiment of the present invention, the template is a biomass-based or polymer-based carbon source.
[0015] According to an embodiment of the present invention, the template is glucose, sucrose, fructose, lignin or polyvinyl pyrrolidone.
[0016] According to an embodiment of the present invention, the swelling agent is thiourea, ammonium chloride, urea or ammonium sulfate.
[0017] According to an embodiment of the present invention, the ratio of the precursor salt to the mixture of the template and the swelling agent is 0.001-10 mol / g.
[0018] According to an embodiment of the present invention, the ratio of the template agent to the bulking agent is 0.001-100 g / g.
[0019] According to an embodiment of the present invention, the pretreatment temperature is 50-250°C.
[0020] According to an embodiment of the present invention, the pretreatment time is 0.5-72h.
[0021] According to an embodiment of the present invention, the calcination annealing process is performed in an oxidizing atmosphere.
[0022] According to an embodiment of the present invention, the oxidizing atmosphere is oxygen or air.
[0023] According to an embodiment of the present invention, the temperature of the calcination annealing treatment is 150-1200°C.
[0024] According to an embodiment of the present invention, the calcination annealing treatment time is 0.5-144h.
[0025] In another aspect of the present invention, the present invention also proposes the use of the rare earth-doped ruthenium-based multi-metal oxide electrocatalyst described above or the rare earth-doped ruthenium-based multi-metal oxide electrocatalyst prepared according to the method described above in zinc-air batteries, electrocatalysis and heterogeneous catalytic reactions.
[0026] In another aspect of the present invention, the present invention also proposes a rare earth doped ruthenium based multinary metal oxide electrocatalyst. According to an embodiment of the present invention, the catalyst is RE-MRuO2, wherein the rare earth element RE includes scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu), and other metals M are Pt (platinum), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn) and bismuth (Bi), etc., and the selected element can be one or more of them.
[0027] According to an embodiment of the present invention, the content of RuO2 in the catalyst material is not less than 50wt%, the content of rare earth elements is between 0-50wt%, and the content of other metals is between 0-50wt%.
[0028] According to an embodiment of the present invention, a method for preparing a rare earth-doped ruthenium-based multinary metal oxide catalyst comprises the following steps:
[0029] (1) A certain proportion of precursor salt is added to the mixture of template and bulking agent, and the mixture is evenly mixed by magnetic stirring / mechanical stirring / ultrasound, etc., wherein the template is a biomass-based or polymer-based carbon source such as glucose / sucrose / fructose / lignin / polyvinyl pyrrolidone, and the bulking agent is an easily decomposable agent such as thiourea / ammonium chloride / urea / ammonium sulfate, and the selected template or bulking agent is not limited to the substances listed above.
[0030] (2) Pretreating the uniformly mixed precursor solution in (1) to obtain a loose and porous mixture with highly dispersed precursor metals.
[0031] (3) After pretreatment, the mixture obtained in (2) is subjected to calcination and annealing treatment to obtain the catalyst, which has a porous foam sheet structure.
[0032] According to an embodiment of the present invention, in step (1), the ratio of the precursor salt to the mixture of the template and the swelling agent is 0.001-10 mol / g, wherein the ratio of the template to the swelling agent is 0.001-100 g / g, and the solvent is an inorganic or organic solvent such as water, ethanol, acetone, and the ratio of the solvent to the precursor mixture is 10-1000 ml / g.
[0033] According to an embodiment of the present invention, in step (2), the pretreatment temperature is 50-250° C. and the time is 0.5-72 h.
[0034] According to an embodiment of the present invention, as described in step (3), the product obtained by pretreatment in (2) is calcined in an oxidizing atmosphere such as oxygen / air, with a calcination temperature of 150-1200° C. and a calcination time of 0.5-144 h.
[0035] According to an embodiment of the present invention, the prepared catalyst is a porous foam sheet structure, which is applied in the field of electrocatalysis, especially in oxygen reduction reaction (ORR) and oxygen generation reaction (OER).
[0036] According to an embodiment of the present invention, the catalyst can be applied to, including but not limited to, an air cathode catalyst in a zinc-air battery.
[0037] According to the embodiments of the present invention, at least one of the following technical effects is achieved:
[0038] (1) The preparation method has the advantages of simple process and operation, low cost and environmental friendliness, low equipment requirements and easy large-scale preparation.
[0039] (2) Relying on the high intrinsic OER activity and stability of RuO2, combined with other metal elements, the catalyst has OER / ORR dual-functional catalytic activity and stability. On this basis, rare earth metal elements are doped to further enhance the catalytic activity and stability.
[0040] (3) As an air cathode catalyst, the assembled zinc-air battery has the characteristics of high energy density, high power and long life, showing great potential in large-scale energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0042] Figure 1 Characterizing the morphology of the catalyst;
[0043] Figure 2 To characterize the OER performance of different metal-doped Ru-Mn catalysts;
[0044] Figure 3 Characterizing the bifunctional ORR and OER performance of the catalyst;
[0045] Figure 4 The open circuit voltage of the zinc-air battery assembled with the catalyst;
[0046] Figure 5 A discharge rate performance curve of a zinc-air battery assembled with the catalyst;
[0047] Figure 6 The constant current charge-discharge cycle stability curve of the zinc-air battery assembled with the catalyst is shown. DETAILED DESCRIPTION
[0048] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0049] Embodiment 1:
[0050] (1) Weigh a certain mass of glucose and urea and dissolve them in deionized water, wherein the mass ratio of glucose to urea is 2:1 (g / g), and the ratio of solvent water to template agent and bulking agent is 3:1 (ml / g).
[0051] (2) Add a certain molar amount of RuCl3, MnSO4 and CeCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the bulking agent is 0.2:5 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0052] (3) The precursor mixture is placed in an oven and pretreated at 150° C. for 12 hours to obtain a loose and porous black-brown substance.
[0053] (4) The pretreated product was placed in a muffle furnace and calcined and annealed at 600° C. for 12 hours in an air atmosphere to obtain the Ce-MnRuO2 catalyst.
[0054] Combination Figure 1 The morphology of the catalyst is characterized. Figure 1 a) shows that the catalyst material presents a porous foam sheet structure, which is formed by the accumulation of nano-scale particles ( Figure 1 b and 1c). The OER performance of different metal-doped ruthenium manganese oxides in 1.0 M KOH electrolyte is characterized as follows Figure 2 , where the overpotential of the rare earth-doped ruthenium manganese catalyst at a current density of 10mA cm-2 is only 265mV, which has obvious advantages. Furthermore, in 0.1M KOH electrolyte, the ORR half-slope potential of the catalyst is 0.859V; at a current density of 10mA cm-2, the OER overpotential of the catalyst is 282mV, which is better than most reported values in the literature; the oxygen potential difference is 0.653V, showing excellent bifunctional catalytic activity ( Figure 3 ). Combined Figure 4-5The catalyst was assembled into a zinc-air battery, whose open circuit voltage was 1.47 V and almost no decay was observed after standing for 120 minutes. -2 After the discharge test under 10mAcm -2 Under the current density, charging and discharging are cycled for 10 minutes each, and there is no obvious change after 500 cycles of stable operation, which fully demonstrates that the zinc-air battery assembled with this catalyst has good stability.
[0055] Embodiment 2:
[0056] (1) Weigh a certain mass of sucrose and ammonium chloride and dissolve them in deionized water, wherein the mass ratio of sucrose to ammonium chloride is 10:1 (g / g), and the ratio of solvent water to template agent and bulking agent is 5:1 (ml / g).
[0057] (2) Add a certain molar amount of RuCl3, NiCl2 and CeCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the bulking agent is 0.2:5 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0058] (3) The precursor mixture is placed in an oven and pretreated at 180° C. for 5 hours to obtain a loose and porous black-brown substance.
[0059] (4) The pretreated product was placed in a muffle furnace and calcined and annealed at 550° C. for 24 hours in an air atmosphere to obtain the Ce-NiRuO2 catalyst.
[0060] Embodiment three:
[0061] (1) Weigh a certain mass of fructose and ammonium carbonate and dissolve them in ethanol, wherein the mass ratio of fructose to ammonium carbonate is 5:1 (g / g), and the ratio of solvent ethanol to template agent and bulking agent is 10:1 (ml / g).
[0062] (2) Add a certain molar amount of RuCl3, MnSO4 and GdCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the bulking agent is 0.2:10 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0063] (3) The precursor mixture is placed in an oven and pretreated at 130° C. for 10 hours to obtain a loose and porous black-brown substance.
[0064] (4) The pretreated product is placed in a muffle furnace and calcined and annealed at 600° C. for 24 hours in an air atmosphere to obtain the Gd—MnRuO 2 catalyst.
[0065] Embodiment 4:
[0066] (1) Weigh a certain mass of glucose and ammonium carbonate and dissolve them in deionized water, wherein the mass ratio of glucose to ammonium carbonate is 10:1 (g / g), and the ratio of solvent water to template agent and bulking agent is 10:1 (ml / g).
[0067] (2) Add a certain molar amount of RuCl3, CoCl3 and LaCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the bulking agent is 0.2:10 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0068] (3) The precursor mixture is placed in an oven and pretreated at 130° C. for 12 hours to obtain a loose and porous black-brown substance.
[0069] (4) The pretreated product is placed in a tubular furnace and calcined and annealed at 350° C. for 24 hours in an oxygen atmosphere to obtain the La-CoRuO2 catalyst.
[0070] Embodiment five:
[0071] (1) Weigh a certain amount of polyvinyl pyrrolidone (PVP) and urea and dissolve them in deionized water, wherein the mass ratio of polyvinyl pyrrolidone (PVP) to urea is 1:1 (g / g), and the ratio of solvent water to template agent and bulking agent is 10:1 (ml / g).
[0072] (2) Add a certain molar amount of RuCl3, FeSO4 and LaCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the bulking agent is 0.2:15 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0073] (3) The precursor mixture is placed in an oven and pretreated at 180° C. for 10 hours to obtain a loose and porous black-brown substance.
[0074] (4) The pretreated product is placed in a muffle furnace and calcined and annealed at 500° C. for 24 hours in an air atmosphere to obtain the La—FeRuO 2 catalyst.
[0075] Embodiment six:
[0076] (1) Weigh a certain mass of glucose and urea and dissolve them in deionized water, wherein the mass ratio of glucose to urea is 2:1 (g / g), and the ratio of solvent water to template agent and bulking agent is 10:1 (ml / g).
[0077] (2) Add a certain molar amount of RuCl3, CuCl2 and CeCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the swelling agent is 0.2:10 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0078] (3) The precursor mixture is placed in an oven and pretreated at 150° C. for 12 hours to obtain a loose and porous black-brown substance.
[0079] (4) The pretreated product was placed in a muffle furnace and calcined and annealed at 500° C. for 12 hours in an air atmosphere to obtain the Ce-CuRuO2 catalyst.
[0080] Embodiment seven:
[0081] (1) Weigh a certain mass of glucose and urea and dissolve them in deionized water, wherein the mass ratio of glucose to urea is 2:1 (g / g), and the ratio of solvent water to template agent and bulking agent is 10:1 (ml / g).
[0082] (2) Add a certain molar amount of RuCl3, CuCl2 and CeCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the swelling agent is 0.2:10 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0083] (3) The precursor mixture is placed in an oven and pretreated at 150° C. for 12 hours to obtain a loose and porous black-brown substance.
[0084] (4) The pretreated product was placed in a muffle furnace and calcined and annealed at 500° C. for 12 hours in an air atmosphere to obtain the Ce-CuRuO2 catalyst.
[0085] Embodiment eight:
[0086] (1) Weigh a certain mass of glucose and thiourea and dissolve them in deionized water, wherein the mass ratio of glucose to thiourea is 2:1 (g / g), and the ratio of solvent water to template agent and bulking agent is 10:1 (ml / g).
[0087] (2) Add a certain molar amount of RuCl3, CuCl2 and EuCl3 to the precursor solution so that the ratio of the precursor metal salt to the template and the swelling agent is 0.2:20 (mol / g), and then fully mechanically stir the mixture to make it uniform.
[0088] (3) The precursor mixture is placed in an oven and pretreated at 140° C. for 12 hours to obtain a loose and porous black-brown substance.
[0089] (4) The pretreated product was placed in a muffle furnace and calcined and annealed at 700° C. for 12 hours in an air atmosphere to obtain the Eu-CuRuO2 catalyst.
[0090] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0091] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A rare earth doped ruthenium-based multinary metal oxide electrocatalyst, characterized in that: The rare earth doped ruthenium based multinary metal oxide electrocatalyst is RE-MRuO2, RE is selected from rare earth elements, M is other metal elements, the content of RuO2 is not less than 50wt%, the content of rare earth elements is between 0-50wt%, and the content of metal elements is between 0-50wt%.
2. The rare earth doped ruthenium based multinary metal oxide electrocatalyst according to claim 1, characterized in that: The rare earth elements include scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu), and the other metals M are one or more of Pt (platinum), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn) and bismuth (Bi).
3. A method for preparing a rare earth-doped ruthenium-based multinary metal oxide electrocatalyst, characterized in that: include: 1) mixing and pretreating a mixture of a precursor salt, a template agent and a bulking agent to obtain a mixture, 2) calcining and annealing the mixture to obtain a rare earth-doped ruthenium-based multinary metal oxide electrocatalyst, Among them, the rare earth doped ruthenium-based multi-metal oxide electrocatalyst is RE-MRuO2, RE is selected from rare earth elements, M is other metal elements, the content of RuO2 is not less than 50wt%, the content of rare earth elements is between 0-50wt%, and the content of other metal elements is between 0-50wt%.
4. The method according to claim 3, characterized in that The rare earth elements include scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu), and the other metals M are one or more of Pt (platinum), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn) and bismuth (Bi).
5. The method according to claim 3, characterized in that: The template agent is a biomass-based or polymer-based carbon source; Optionally, the template is glucose, sucrose, fructose, lignin or polyvinyl pyrrolidone.
6. The method according to claim 3, characterized in that The bulking agent is thiourea, ammonium chloride, urea or ammonium sulfate.
7. The method according to claim 3, characterized in that The ratio of the precursor salt to the mixture of the template and the bulking agent is 0.001-10 mol / g; Optionally, the ratio of the templating agent to the bulking agent is 0.001-100 g / g.
8. The method according to claim 3, characterized in that The pretreatment temperature is 50–250°C; Optionally, the pretreatment time is 0.5-72h.
9. The method according to claim 3, characterized in that: The calcination annealing treatment is carried out in an oxidizing atmosphere; Optionally, the oxidizing atmosphere is oxygen or air; Optionally, the temperature of the calcination annealing treatment is 150-1200°C; Optionally, the calcination annealing treatment time is 0.5-144h.
10. Use of the rare earth-doped ruthenium-based multinary metal oxide electrocatalyst according to any one of claims 1 to 2 or the rare earth-doped ruthenium-based multinary metal oxide electrocatalyst prepared by the method according to any one of claims 3 to 9 in zinc-air batteries, electrocatalysis and heterogeneous catalytic reactions.
Citation Information
Patent Citations
Bifunctional oxygen electrocatalyst and preparation and application thereof
CN112758996A
Transition metal doped ruthenium oxide nano material, and preparation method and application thereof
CN115196697A
Ce-doped RuO2 bimetallic oxide as well as preparation method and application thereof
CN115976540A
Rare earth Ce-doped RuO2 catalyst as well as preparation method and application thereof
CN117107252A
Rare earth element doped RuO2 material as well as preparation method and application thereof
CN118127561A